2004
DOI: 10.1166/jnn.2004.051
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Carbon Nanotubes in High Electric Fields

Abstract: The influence of electric fields on carbon nanotubes is experimentally demonstrated. Alignment of nanotubes along field lines, directed motion of nanotubes between electrodes separated by several thousand micrometers, and impressive solid-state actuation behavior of nanotube-embedded structures are demonstrated, taking into account the polarization and charging of the nanotubes. These effects are reported for long strands of nanotubes, nanotubes dispersed on substrates, and nanotube-embedded polymer strips. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These observations may lead to novel electromechanical applications for CNTs. 85 Mechanically, CNTs are currently the strongest known fibers because the carbon-carbon bond observed in graphite is one of the strongest in nature. Elastic properties of CNTs can be obtained from experiment by assuming them structural members.…”
Section: Properties Of Carbon Nanotubesmentioning
confidence: 99%
“…These observations may lead to novel electromechanical applications for CNTs. 85 Mechanically, CNTs are currently the strongest known fibers because the carbon-carbon bond observed in graphite is one of the strongest in nature. Elastic properties of CNTs can be obtained from experiment by assuming them structural members.…”
Section: Properties Of Carbon Nanotubesmentioning
confidence: 99%
“…In the case of applying DC electrical field, however, the unidirectional alignment of CNFs does not always occur because CNFs are charged in suspension and thus may migrate to one electrode (16,17) .…”
Section: In-situ Observation Of Alignment Processmentioning
confidence: 99%
“…These mechanisms were observed to promote alignment in solid CNTs and in CNTs suspended in liquids [4,[17][18][19]. A bottom layer consisting mainly of silicone oil where the shear stress is significantly decreased is therefore obtained.…”
Section: Electrorheologial Properties Of Nano Laden Suspensionsmentioning
confidence: 99%
“…Researchers are especially keen on nanomaterials as sensors and actuators. Recent results have shown that carbon nanotubes possess significant potential as solidstate actuators with mechanical response to applied electric fields [1][2][3][4]. The discovery of carbon nanotubes (CNT), carbon nanofibers (CNF) and most recently the development of a variety of nanowire materials (NW) [5][6][7], including Si, Ge, and GaAs, is playing a key role in the progress of exciting research in nanoreinforced systems given their remarkable electrical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%